Use of COVID-19 Personal Protective Equipment (PPE) Among Healthcare Workers in Teaching Hospitals of Khorramabad, Iran - Zibaei, Mehdi; Halimi, Shahnaz; Rezaei, Faranak; Shakib, Pegah; Soroush, Setareh (Coronaviruses, 2024)
Background and Objective: In light of the pivotal role played by personal protective equipment (PPE) in mitigating the transmission of the novel coronavirus, this study aimed to investigate the utilization of personal protective equipment in the context of the COVID-19 pandemic among medical personnel and students affiliated with Lorestan University of Medical Sciences in the year 2019. Methods: This cross-sectional, descriptive research study collected essential data, encompassing personal characteristics and inquiries concerning the use of personal protective equipment, the extent of their utilization, training regarding proper equipment use, and adherence to health guidelines, including hand hygiene and disinfectant usage. Data were gathered through a questionnaire developed in accordance with international standards, specifically the PPE Safe Survey. The questionnaire was administered to medical staff, including physicians, nurses, and medical students, working in healthcare facilities that admitted COVID-19 patients within the Lorestan University of Medical Sciences, situated in Khorramabad. Results: Our investigation involved a total of 201 participants, comprising 82 (40.8%) males and 119 (59.2%) females. The average age of the participants was 32 years, with an average daily duration of personal protective equipment utilization amounting to 8.9 hours. Notably, 44 (21.9%) participants worked in emergency wards, 63 (31.3%) in general medical wards, 12 (6.0%) in administrative departments, 14 (7.0%) in surgical units, 11 (5.5%) in anesthesiology, 17 (8.5%) in intensive care units, and 40 (19.9%) in miscellaneous contexts. Conclusion: The study findings underscore the imperative need for healthcare professionals to consistently employ suitable personal protective equipment, encompassing face masks, eye protection, gowns, and eye shields. Furthermore, our study highlights the significance of appropriate training and rigorous adherence to equipment utilization protocols during healthcare tasks, coupled with consistent hand hygiene practices in healthcare facilities.
Keywords: pandemic